Understanding Corporate Purpose: Lessons from Aotearoa New Zealand’s Reform Debate on Directors’ Duties - Solinas, Matteo; Lin, Da (Victoria University of Wellington Law Review, 2025)
This is the foreword to the special issue based on the conference Symposium on Corporate Purpose, which took place in Wellington in July 2024 and was jointly organised by Te Herenga Waka | Victoria University of Wellington and the University of Richmond School of Law. The discussions from the Symposium are captured within the various pieces within this special issue.